Real-World Safety and Efficacy of Transcatheter Mitral Valve Repair With MitraClip: Thirty-Day Results From the Italian Society of Interventional Cardiology (GIse) Registry Of Transcatheter Treatment of Mitral Valve RegurgitaTiOn (GIOTTO) - Bedogni, Francesco; Testa, Luca; Rubbio, Antonio Popolo; Bianchi, Giovanni; Grasso, Carmelo; Scandura, Salvatore; De Marco, Federico; Tusa, Maurizio; Denti, Paolo; Alfieri, Ottavio; Giordano, Arturo; Ferraro, Paolo; et al. (Cardiovascular revascularization medicine, 2020)
Available scientific evidence of transcatheter mitral valve repair with the MitraClip comes from randomized controlled trials, which showed controversial results that hardly translate into real-world practice, and from registries of relatively small sample size. To collect real-world data in a multicenter, prospective, country-level registry. The Italian Society of Interventional Cardiology (GIse) Registry Of Transcatheter Treatment of Mitral Valve RegurgitaTiOn (GIOTTO) is an ongoing single-arm, multicenter, prospective registry that started enrollment in February 2016. Clinical end points were defined according to the Mitral Valve Academic Research Consortium (MVARC) criteria. From February 2016 to December 2018, 1189 patients (mean age 76 ± 9.1 years) were enrolled. The main MR etiology was functional (64.9%). MVARC technical success was 96.6%. At 30-day follow-up (n = 1131), MVARC device and procedural success were 92.5% and 87% respectively, and all-cause death was 3%. The majority of patients who died at 30-day had functional MR (69.7%). Mixed etiology (OR 0.94, 95% CI 0.02–0.61) and prolonged length of stay in ICU (OR 0.97, 95% CI 0.95–0.99) were found to be negative independent predictors of device success at 30-day. The EuroSCORE II (OR 0.96, 95% CI 0.93–0.99), LVEDV-I (OR 0.99, 95% CI 0.98–0.99) and prolonged length of stay in ICU (OR 0.98, 95% CI 0.97–0.99) were negative independent factors of MVARC procedural success at 30-day. The GIOTTO registry is one of the largest prospective registries available on MitraClip and shows favorable acute and 30-day safety and efficacy. •Mitral regurgitation is the most common cardiac valve disease with a prevalence of 9.3% in subjects ≥75 years of age.•Given the contrasting data coming from randomized controlled trials, multicenter registries maintain an important role to better depict the safety/efficacy profile of the MitraClip procedure.•The GIse registry Of Transcatheter treatment of mitral valve regurgitaTiOn (GIOTTO) is one of the largest real-world studies in MR patients (n = 1189) treated with the MitraClip.•The functional mitral regurgitation was the principal indication to MitraClip procedure in patients at high surgical risk or not suitable for surgery.•The Mitraclip procedure was safe and effective, as indicated by the high rate of technical (96.6%), device (92.5%) and procedural (87%) success.